(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2012)
Following the correspondence between Boehm and Mitchell, the paper discusses some focal points related to the so-called iconic, or pictorial turn: the difficulty in writing a history of the Bildwissenschaft, the role of the medieval studies, affinities and differences between the European and the American approach to image (and between Boehm’s and Mitchell’s approach), the Italian and French reception, the meaning to attribute to the word ‘turn’, and the relationship among the iconic or pictorial turn, the visual studies and more traditional disciplines such as aesthetics and art history.